Hierarchical Hollow Spheres of Fe2O3@Polyaniline for Lithium Ion Battery Anodes. (21st August 2013) - Jeong, Jae‐Min; Choi, Bong Gill; Lee, Soon Chang; Lee, Kyoung G.; Chang, Sung‐Jin; Han, Young‐Kyu; Lee, Young Boo; Lee, Hyun Uk; Kwon, Soonjo; Lee, Gaehang; Lee, Chang‐Soo; Huh, Yun Suk
<x xml:space="preserve">Abstract</x> Hierarchical hollow spheres of Fe2O3@polyaniline are fabricated by template‐free synthesis of iron oxides followed by a post in‐ and exterior construction. A combination of large surface area with porous structure, fast ion/electron transport, and mechanical integrity renders this material attractive as a lithium‐ion anode, showing superior rate capability and cycling performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>